2020
DOI: 10.1021/acs.jnatprod.9b01011
|View full text |Cite
|
Sign up to set email alerts
|

Meliponamycins: Antimicrobials from Stingless Bee-Associated Streptomyces sp.

Abstract: Social insects establish complex interactions with microorganisms, some of which play defensive roles in colony protection. The important role of pollinators such as the stingless bee Melipona scutellaris in nature encouraged us to pursue efforts to study its associated microbiota. Here we describe the discovery of two novel cyclic hexadepsipeptides, meliponamycin A (1) and meliponamycin B (2), from Streptomyces sp. ICBG1318 isolated from M. scutellaris nurse bees. Their structures were established by interpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 31 publications
(55 reference statements)
1
22
0
2
Order By: Relevance
“…The novel cyclodepsipeptides named meliponamycin A (40) and meliponamycin B (41) (▶ Fig. 3) were strongly active against P. larvae and human pathogens, such as Staphylococcus aureus and L. infantum [92].…”
Section: Natural Products Mediating Microbial Symbiosis In Stingless mentioning
confidence: 99%
“…The novel cyclodepsipeptides named meliponamycin A (40) and meliponamycin B (41) (▶ Fig. 3) were strongly active against P. larvae and human pathogens, such as Staphylococcus aureus and L. infantum [92].…”
Section: Natural Products Mediating Microbial Symbiosis In Stingless mentioning
confidence: 99%
“…The elution order of the Marfey’s products of piperazic acid was empirically reported in a structural study of the piperazic acid-bearing cyclic peptide dentigerumycin, with authentic l - and d -piperazic acids; the l -Marfey’s product of ( R )-piperazic acid elutes faster than the d -Marfey’s product, whereas the d -Marfey’s product of ( S )-piperazic acid elutes before the l -Marfey’s product by reversed-phase HPLC. Since this first report of Marfey’s analysis of piperazic acids, this elution order has been widely used for the configurational determination of piperazic acid moieties in natural products. …”
mentioning
confidence: 99%
“…It has also been reported that the symbiotic Streptomyces bacteria, located in specialized antennal glands, excrete antibiotics to protect wasp larvae from pathogenic fungal infestation (Kaltenpoth et al, 2005;Kroiss et al, 2010). Furthermore, studies have shown that the stingless bees, Melipona scutellaris, engage in defensive symbiosis with actinobacteria that produce antibacterial small molecules including the lobophorin, anthracycline, and cyclic hexadepsipeptide families, helping to protect their colonies against the entomopathogenic Paenibacillus larvae (Rodríguez-Hernández et al, 2019;Menegatti et al, 2020).…”
Section: Introductionmentioning
confidence: 99%